Developing Nigerian communities through community government council: The Imo state experience. Issue 5 (19th October 2020) - Mbah, Peter O.; Obiagu, Uchenna C.
ABSTRACT: The recent establishment of community government as a distinct, but coordinating level of government in Nigeria came with the high expectation that it would facilitate adequate transfer of statutory powers, responsibilities, and finances to various communities for community-driven development. However, the underdevelopment situation of most of the communities seemingly appears to have dashed this expectation. Thus, this recent study investigated the development essence of community government as decentralized local governance with a view to unraveling factors responsible for perceived poor performance. Using mixed data and first-hand insights from multi-stakeholder forum premised on the theory of post-colonial state as our analytical framework, the study argued that community government grossly underperformed its development functions, arising from a lack of stakeholders' supports and occasioned by state government interference in community government administration. The implication of this finding is that community government should be determined and driven on the basis of collective stakeholder engagement within the novel framework of community-driven development.